Polluting our rivers in search of gold: how sustainable are reforms to stop informal miners from returning to mining sites in Ghana? - Mensah, Albert Kobina; Tuokuu, Francis Xavier Dery (Frontiers in Environmental Science, 2023)
Even though artisanal gold mining has helped many people in rural areas around the world make a living, it has also destroyed and polluted many water bodies. This paper uses Prestea in the southwestern part of Ghana to show how artisanal gold mining has led to the pollution of freshwater bodies and the ecosystem as a whole. A non-probabilistic purposive sampling technique was used for the selection of nine artisanal gold mining communities for the survey. Primary data consisted of participant observation and in-depth interviews with local actors in gold mining communities. Secondary data included policies and legal documents, media websites, and reports on environmental assessments of various artisanal gold mining sites. We observed that artisanal gold mining activities (‘galamsey’) have led to substantial pollution and depletion of the water resources in and around the surrounding mining areas in Prestea. The two major water bodies, which used to serve as major sources for drinking, cooking, and bathing, have ended up being heavily polluted and highly degraded as a result of the irresponsible mining activities. To achieve benign production, the Ghanaian government over the years has made efforts to formalize the operations of galamsey activities through six main routes: policy intervention, a complete ban on their activities, military strategy, national dialogue, alternative livelihood programs, and community mining. We evaluate how long these measures will last and end the study with some policy and practical suggestions for making the artisanal mining sector in Ghana more official. These suggestions could be used in other countries in the global south as well. We also provide avenues for future research.